The rhetoric of disenchantment through symbolism - Munyangeyo, Théophile (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2012)
The symbolism of flowers has always been a significant part of cultures around the world due to their functional meaning in daily life. From their decorative to their aromatic role, flowers and their symbolic meaning trigger emotions, convey wishes and represent thoughts that can not be explicitly expressed. In this regard, an elaborate language based on flower symbolism was developed in many societies, to convey clear messages to the recipient. However, in some cultural contexts, although the flower symbolism has social connotations, it is mainly associated with economic references. As flowers are an essential precursor to fruits, they are inevitably a source of expectations and hence foster a set of hopes and dreams, which can ultimately lead to excitement or disappointment. Through a discourse analysis based on factional narratives, this article explores the parameters through which the symbolism of bifaceted meaning of flowers fictionalises a space that refers to the social reality. This association between the fictional world and social reference has highlighted that writing can profoundly be a means of representing social events through the rhetoric of symbolism. Through a sociological reading approach, this paper aims to analyse how the symbolism of flowers informs the rhetoric of disenchantment that can foster a content-based pedagogy in language learning where silencing practices engender imagery to exercise the freedom of expression.
Keywords: disenchantment; discourse analysis; representation; sociological reading; symbolism